A corpus-based study of word-formation creativity in Facebook Philippine English - Nimfa G. Dimaculangan; Michelle B. Sarmiento (International Journal of Evaluation and Research in Education (IJERE), 2024)
This paper is a study of English as a second language (ESL) teachers’ and students’ newly coined Facebook (FB) lexical items and expressions. It presents sample FB Philippine English (PhilE) words found in ESL teachers’ and students’ FB posts and messages and the formation mechanisms evident in the lexical items. The lexical items are culled from the researchers-built 50,000-word corpus of FB and FB Messenger conversations posted and sent by the mentioned texts’ contributors from the last quarter of 2016 to 2022. The PhilE neologisms are identified from their surrounding English lexical items and analyzed based on a proposed framework for PhilE word-formation processes, and ESL Englishes well-motivated innovations and criteria in standardizing its usages. Data analysis reveals over a hundred PhilE lexical items that are coined through the analytical frameworks used with the present paper’s additional proposed processes for FB lexical formation, hypocoristic extension, and anagrammatic transposition or backward spelling. The lexical items, in general, are colloquial, marking the informality of the FB PhilE register, although written in English. In terms of lexicon, it is advanced that FB English in the country is a variety of Internet PhilE, which should be taught in Sociolinguistics and ESL classrooms.